Direct Democracy and Women's Political Engagement. Issue 3 (12th March 2019) - Kim, Jeong Hyun
Abstract: What are the conditions that promote gender equality in political participation? In this article, I propose that the presence of direct democracy expands gender equality in political participation by signaling the system's openness to women's voice, confirming their political competency, and highlighting their stake in political decisions. To test this argument, I leverage a quasi‐experiment in Sweden in the aftermath of the introduction of universal suffrage, where the type of municipal political institutions was determined by a population threshold. My findings lend strong support to the effect of direct democracy on the political inclusion of women. I find that the gender gap in electoral participation was smaller in municipalities using direct democracy than in similarly sized municipalities that only had representative institutions.